PEMANFAATAN PYTHON DASAR BAGI CIVITAS AKADEMIKA UNIVERSITAS BILLFATH - Yaqin, Ainul; Anggita, Sharazita Dyah; Umam, Ahmad Khairul; Daniswara, Krisna Adilia (Jurnal Abdi Insani, 2024)
In an increasingly advanced digital era, academic institutions around the world face large amounts of data that can be used to improve performance effectiveness. Through Data Science, data types, assumptions and analysis will be visible using one of the languages that is considered easy to learn, namely Python. The aim of this activity is to provide education and training to the Billfath University academic community regarding the use of Data Science using the Python programming language. This community service activity was carried out with an online webinar Introduction to Basic Python for Beginners. The webinar that will be held will discuss the basics of using tools using Jupyter for participants. Based on the priority problems found, activities were carried out to educate the Billfath University academic community about the importance of implementing data science in their respective fields of study. The basic material provided includes how to install and run the tools. The various libraries contained in it are also explained. Other basic materials provided are Data Profiling, Data Scaling, Data Correlation, Data Visualization and Training. The feedback given by the participants was quite positive as evidenced by the enthusiasm in the question and answer session accounting for more than 25% of the total participants. Community service activities in the form of a Python Training Webinar for Beginners were able to educate the Billfath University academic community about the importance of implementing data science in their respective fields of study. In the future, it is hoped that Billfath University will be able to increase the skills of its resources in the field of data science by holding more technical workshops for participants.